A pathway independent multi-modular ordered control system based on thermosensors and CRISPRi improves bioproduction in Bacillus subtilis. Issue 11 (7th June 2022) - Yu, Wenwen; Jin, Ke; Wu, Yaokang; Zhang, Quanwei; Liu, Yanfeng; Li, Jianghua; Du, Guocheng; Chen, Jian; Lv, Xueqin; Ledesma-Amaro, Rodrigo; Liu, Long
Abstract: Dynamic regulation is an effective strategy for control of gene expression in microbial cell factories. In some pathway contexts, several metabolic modules must be controlled in a time dependent or ordered manner to maximize production, while the creation of genetic circuits with ordered regulation capacity still remains a great challenge. In this work, we develop a pathway independent and programmable system that enables multi-modular ordered control of metabolism in Bacillus subtilis . First, a series of thermosensors were created and engineered to expand their thresholds. Then we designed single-input-multi-output circuits for ordered control based on the use of thermosensors with different transition points. Meanwhile, a repression circuit was constructed by combining CRISPRi-based NOT gates. As a proof-of-concept, these genetic circuits were applied for multi-modular ordered control of 2′-fucosyllactose (2′-FL) biosynthesis, resulting in a production of 1839.7 mg/l in shake flask, which is 5.16-times that of the parental strain. In a 5-l bioreactor, the 2′-FL titer reached 28.2 g/l with down-regulation of autolysis. Taken together, this work provides programmable and versatile thermosensitive genetic toolkits for dynamic regulation in B. subtilis and a multi-modular ordered control framework that can be used to improve metabolic modules in other chassis cells and for other compounds.